Dietary habits in children from rural environments - Sygit, Katarzyna (Polish Journal of Public Health, 2009)
Aim. This representative study aimed at diagnosing the dietary habits of children living in rural environments and at determining the relationships of these behaviours with a range of descriptive variables. Methods. The study was carried out among children and their parents living in 7 rural counties within the Western Pomeranian Voivodeship. The final analysis included 1,351 children under the age of 14, along with their parents (1,351). Results. The research has pointed that 83.12% of the children consume breakfast before heading for school, with 16.88% not eating breakfast at all. Parents provide their children with a packed lunch or snack in 73.53% of cases. One or two meals daily are eaten by 118 of the children (2.46%); however, the largest group of children (42.97%) eat four meals per day. Over a third (34.94%) eat sweets on a daily basis, with only 2.08% never eating them. Only 32.19% drink milk every day (i.e. 1547 people), with daily consumption of fruit and vegetables at only 56.35% of the subjects, and 3.47% never eating them. In the parents’ view, 23.99% believe their children have a very good diet, while 57.99% think that their children’s diet is good. It was also found that dietary habits depend on such descriptive variables as gender, parental educational levels, type of household or the household’s living conditions. Conclusions. There is a considerable predominance of anti-health over health-promoting behaviours. There is also a significant relationship between the children’s health behaviours and their gender, their parents’ educational levels and their family standard of living.